(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2022)
This article aims to share reflections on the studies of Dances of Black families. To achieve this, the process of teaching-learning of São Gonçalo de Amarante Dance, a kind of family manifestation produced in the Quilombola settlement of Mussuca in Laranjeiras, Sergipe – Brazil, was observed. We started with the question "how do children learn to dance the São Gonçalo Dance in the family context of Mussuca?". It was considered that the fundamentals concerning the learning of the São Gonçalo Dance are based on processes linked to empirical practice, repetition and family experience. Furthermore, notes were established for the definition of Black family dances and the practices related to the learning of these dances were discussed through a study focused on the São Gonçalo de Amarante Dance.